Arahan Pengembangan Ruang Terbuka Hijau di Kota Makale Kabupaten Tana Toraja: Studi Kasus: Kelurahan Bombongan - Requelmy TulungAllo, Gebryl; Syafri, Syafri; Ruslan, Rusneni (Fakultas Teknik Universitas Bosowa, 2024)
The goal of this study is to examine the major causes impacting the absence of green open space in Makale City and to suggest strategies for the development of green open space in Makale City. This research technique is a quantitative-methods. The Chi-Square analysis tool was used to assess the key elements impacting the shortage of green open space in Makale City, while descriptive qualitative analysis was utilized to generate suggestions for the development of green open space in Makale City. The fundamental conclusion of this study is that, based on the Chi-Square results, the element of land availability has a substantial effect on the absence of variable Y or Green Open Space (RTH). Meanwhile, education is a crucial element influencing the absence of Green Open Space (RTH). The Regional Government as the manager of Green Open Spaces in Makale City, issuing regional regulations or planning documents related to the utilization of regional Green Open Spaces in Tana Toraja Regency, and the Regional Government as the person in charge of providing Green Open Spaces (RTH) in urban areas are the directions for the development of green open spaces in Makale City. Makale Kelurahan Bombongan immediately resolves problems related to inadequate land in Makale City and increases the number of green open spaces to meet the minimum quota of green areas, and re-evaluates green open spaces (RTH) in Makale urban areas with reference to the relevant regulations